2018
DOI: 10.1039/c8dt01292j
|View full text |Cite
|
Sign up to set email alerts
|

Anion-induced 3d–4f luminescent coordination clusters: structural characteristics and chemical fixation of CO2 under mild conditions

Abstract: Two series of anion-induced 3d-4f luminescent clusters ZnII2LnIII2L4 (LnIII = Eu3+, Tb3+, Er3+, Yb3+, Nd3+) and ZnII4LnIII2L4 (LnIII = Tb3+, Nd3+) based on μ3-OH group were synthesized and characterized. The difference in anions not only leads to significant structural changes, but also changes the luminescent properties of the 3d-4f coordination clusters. These complexes show excellent catalytic performance for CO2 conversion to obtain cyclic carbonates with wide substrate scopes and high selectivity under mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 69 publications
(3 reference statements)
0
25
0
Order By: Relevance
“…LOCs have also been explored in this capacity. For example, Zhang et al reported two series of heterometallic LOCs, namely Ln 2 Zn 2 (µ 3 -OH) 2 (L 1 ) 4 (NO 3 ) 4 (Ln 2 Zn 2 , Ln = Eu, Tb, Er, Yb, Nd, HL 1 = Methyl-3-methoxysalicylate, Figure 3) and Ln 2 Zn 4 (µ 3 -OH) 2 (L 1 ) 4 (OAc) 6 (NO 3 ) 2 (Ln 2 Zn 4 , Ln = Tb, Nd), and studied their applications for the CO 2 and epoxide cycloaddition (Figure 4) [33]. All these cluster complexes have been shown to heterogeneously catalyze the reaction with Tb 2 Zn 2 being most effective, producing a turnover number (TON) of 9260 and a turnover frequency (TOF) of 661 h −1 in a 12 h reaction.…”
Section: Catalytic Cycloaddition Of Co 2 and Epoxidesmentioning
confidence: 99%
“…LOCs have also been explored in this capacity. For example, Zhang et al reported two series of heterometallic LOCs, namely Ln 2 Zn 2 (µ 3 -OH) 2 (L 1 ) 4 (NO 3 ) 4 (Ln 2 Zn 2 , Ln = Eu, Tb, Er, Yb, Nd, HL 1 = Methyl-3-methoxysalicylate, Figure 3) and Ln 2 Zn 4 (µ 3 -OH) 2 (L 1 ) 4 (OAc) 6 (NO 3 ) 2 (Ln 2 Zn 4 , Ln = Tb, Nd), and studied their applications for the CO 2 and epoxide cycloaddition (Figure 4) [33]. All these cluster complexes have been shown to heterogeneously catalyze the reaction with Tb 2 Zn 2 being most effective, producing a turnover number (TON) of 9260 and a turnover frequency (TOF) of 661 h −1 in a 12 h reaction.…”
Section: Catalytic Cycloaddition Of Co 2 and Epoxidesmentioning
confidence: 99%
“…108 So far there have been two reports of 3d-4f CCs used as catalysts for the cycloaddition of styrene oxides and CO2 to obtain cyclic carbonates. 109,110 The first of these described two isoskeletal heptanuclear 3d-4f CCs, which were synthesised from the "helical" HL31 ligand 2(μ3 -OH)2(L32)4(OAc)6(NO3)2] (39-ZnLn) respectively are described (Figure 9). Single-crystal X-ray structural analysis and a variety of characterisation methods were used to confirm the structure of all these 3d-4f CCs and revealed the two metal centres of Ln and Zn were situated in the correct range to enable synergistic action as Lewis acid activators.…”
Section: D-4f CC For Carbon Dioxide Fixationmentioning
confidence: 99%
“…7 Our group has established the efficacy of a series of tetranuclear [M II 2Ln III 2L4(X)2(solv)2] (M = Ni, Co, Cu, Zn, X = Cl, NO3, Ln = Y, Dy, Gd) for domino-electro cyclization and Lewis acid reactions, [8][9][10][11] whereas other groups have, successfully, used them in redox, [12][13][14] co-polymerization 15 and carbon dioxide fixation reactions. 16,17 The metal-promoted Suzuki-Miyaura coupling includes organoboron derivatives and carbon electrophiles, and represents a valuable procedure for a C-C bond formation (Scheme 1). 18 This synthetic protocol uses commercially available boron reactants, which are relatively stable, non-toxic and can be easily functionalized.…”
Section: The Air Stable and High Yielding Tetranuclear Coordination Cmentioning
confidence: 99%